Fertility and Economic Instability: The Role of Unemployment and Job Displacement - Emilia Del Bono; Andrea Weber; Rudolf Winter-Ebmer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
We study the effect of job displacement on fertility in a sample of white collar women in Austria. Using instrumental variables methods we show that unemploy- ment incidence as such has no negative effect on fertility decisions, but the very fact of being displaced from a career-oriented job has; fertility rates for women affected by a plant closure are signiffcantly below those of a control group, even after six years.
Keywords: J13; J64; J65; J24; 330; fertility; unemployment; plant closings; human capital